Effect of Stent Strut Interval on Neointima Formation After Venous Stenting in an Ovine Model. (August 2021) - Jalaie, Houman; Schleimer, Karina; Toonder, Irwin M.; Gombert, Alexander; Afify, Mamdouh; Doganci, Suat; Modabber, Ali; Razavi, Mahmood K.; Barbati, Mohammad E.
Abstract : Objective: The impact of stent design on venous patency is not well studied. The purpose of this study was to investigate the effect of stent material burden on endothelial coverage of stented venous segments, which may contribute to vessel healing and patency. Methods: Segmented self expanding bare nitinol stents (18 × 50 mm) comprising 5 mm long attached metallic rings separated by 2, 5, or 8 mm gaps were implanted in the inferior vena cava (IVC) of 10 sheep. These stents were designed and manufactured for the purposes of this study. At six, 12, and 24 weeks after implantation the animals were euthanised and the stented vessels harvested for histomorphometric analysis. Three sections from the metallic part as well as the gaps between the struts were reviewed for quantification of endothelialisation after six, 12, and 24 weeks. The intimal thickness over and between the stent struts was measured. The endothelialisation score (graded from 1 for complete luminal endothelialisation to 5 for absence of endothelial cells) was determined. Results: All stents were successfully deployed and all 10 sheep survived until the time of harvesting. Macroscopic inspection after 24 weeks showed only partial endothelialisation over stents with 2 mm and 5 mm skipped segments, whereas the stents with 8 mm skipped segments were totally incorporated into the vein wall. After 24 weeks, the mean (SD) neointimal thicknesses over stent struts with 2 mm, 5 mm, and 8 mm skipped segments were 254.0 (51.6), 182.2 (98.1), and 194.6 (101.1) μm, respectively. Comparison of endothelialisation scores of stents over time showed statistically significantly better endothelialisation over stents with 8 mm gaps after 12 and 24 weeks. Conclusion: Stent designs providing structural support to veins with larger gaps between the scaffold material appear to lead to faster and more complete endothelialisation as well as a thinner intimal layer.